Implementasi Kebijakan Pengelolaan Dana Bantuan Operasional (BOS) pada UPT SMP Negeri 31 Gresik - Anis Sa'adah (Universitas Muhammadiyah Gresik, 2025)
This research was conducted at UPT SMP Negeri 31 Gresik. This research took place from December 2024 until completion. The background of this research is based on the author's interest in conducting research on the Implementation of the Operational Assistance Fund Management Policy (BOS) at UPT SMP Negeri 31 Gresik. This study aims to identify how the policy is implemented, assess its effectiveness, and determine the challenges faced during the implementation process. The analysis method used in this study is a qualitative method, namely a method used to analyze and compile arguments by describing, comparing, interpreting data and linking it to theory, then drawing conclusions and suggestions. The data collection method in this study was carried out through observation, interviews, and documentation, and using data related to the implementation of the BOS fund management policy at UPT SMP Negeri 31 Gresik. The informants involved included the principal, BOS treasurer, Dapodik operator, and several teachers. The results of the study indicate that the implementation of the BOS fund management policy at UPT SMP Negeri 31 Gresik has been running according to established procedures, although there are several obstacles in its implementation. Therefore, effective communication is needed between the principal, teachers, and parents, timely distribution of funds, and competent officers to ensure that the management of BOS funds can run optimally.